Hydrogel-Assisted Antisense LNA Gapmer Delivery for In Situ Gene Silencing in Spinal Cord Injury - Moreno, PM (2018)
After spinal cord injury (SCI), nerve regeneration is severely hampered due to the establishment of a highly inhibitory microenvironment at the injury site, through the contribution of multiple factors. The potential of antisense oligonucleotides (AONs) to modify gene expression at different levels, allowing the regulation of cell survival and cell function, together with the availability of chemically modified nucleic acids with favorable biopharmaceutical properties, make AONs an attractive tool for novel SCI therapy developments. In this work, we explored the potential of locked nucleic acid (LNA)-modified AON gapmers in combination with a fibrin hydrogel bridging material to induce gene silencing in situ at a SCI lesion site. LNA gapmers were effectively developed against two promising gene targets aiming at enhancing axonal regeneration—RhoA and GSK3ß. The fibrin-matrix-assisted AON delivery system mediated potent RNA knockdown in vitro in a dorsal root ganglion explant culture system and in vivo at a SCI lesion site, achieving around 75% downregulation 5 days after hydrogel injection. Our results show that local implantation of a AON-gapmer-loaded hydrogel matrix mediated efficient gene silencing in the lesioned spinal cord and is an innovative platform that can potentially combine gene regulation with regenerative permissive substrates aiming at SCI therapeutics and nerve regeneration.